Let’s analyze the year passed - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
While we move ahead with the year 2009, let’s devote some time analyzing the year ended. This stock-taking is prudent to all the stakeholders of AJP, particularly, as AJP still does not enjoy impact factor ratings.